THE PRACTICE-ORIENTED APPROACH TO LEARNING IN EUROPE (Conferencea, 2023)
The article shows the difference and the similarities of the educational methods of European educational system. British philosophers, educators and sociologists, pointing to the crisis situation in the moral sphere of society, pay great attention to the axiological aspect in the development of the teacher's personality, who is ready not only for continuous self-improvement and professional self-actualization, but also dedicates .for the formation of schoolchildren's value orientations of learning